MOSES TO JOSHUA SUCCESSION MODEL IMPLEMENTING VISION INTEGRITY AND PASSION FOR CHRISTIAN LEADERSHIP - Yuco Aldelina; Stella Leoni (Scriptura Indonesia, 2026)
The primary objective of this research is to analyze the leadership succession model from Moses to Joshua, specifically examining the implementation of Vision, Integrity, and Passion (VIP) variables to address modern Christian leadership crises. Contemporary leadership in religious institutions often manifests a